Essays on monetary and fiscal policies in a small open economy - Alves, Renan Santos (2022)
In the first chapter we evaluate the relative importance of domestic and external factors to explain the dynamics of the natural rate of interest in Brazil. We estimate a medium-scale New Keynesian model open economy (DSGE) for Brazil to assess the natural rate of interest and how external factors contribute to explaining its dynamics. Our findings show that the natural rate of interest has declined over the past twenty years. In addition to varying widely over the years, the main drivers are the country risk premium and foreign interest rate. The permanent productivity shock is not relevant to explain the natural rate which suggests the secular stagnation hypothesis does not apply to Brazil. In the second chapter we estimate a small open economy model to study the impact of the interaction between monetary and fiscal policy in Brazil after adopting the Inflation Targeting Regime. The New Keynesian model allows for an active monetary and passive fiscal (AMPF) regime, a passive monetary and active fiscal (PMAF) regime, and a passive monetary and passive fiscal (PMPF) regime. Furthermore, we verified the theoretical framework proposed by Blanchard(2005) for the Brazilian economy. The results suggest that the active monetary and passive fiscal policy are preferred after the Inflation Target was adopted. Additionally, in the PMAF regime the perverse effects of the unexpected monetary shock appear: the increase in the interest rate increases the probability of debt default which makes domestic bonds riskier, increasing the risk premium, and with that, the exchange rate depreciates, generating more inflation. In the last chapter we study the effects of the interaction between monetary and fiscal policy in the Brazilian economy by using structural VARs. We separate the economic regimes through identification by imposing sign and zero restrictions on the systematic monetary and fiscal policy components. Using data after the Inflation Target regime, we find that an increase in the interest rate induces a contraction in output and inflation and depreciates the exchange rate under AMPF and PMAF regimes. A contractionary fiscal shock reduces output but not inflation, in both regimes. Therefore, monetary policy is the best option to reduce inflation in the both regimes.